The Effect of Energy Consumption on Output: A Panel Data Study of Manufacturing Industries in Egypt - Al-Ayouty, Iman (European Journal of Sustainable Development, 2020)
Subsidizing electricity and non-electrical energy products has affected manufacturing output in Egypt, especially given the structure of Egypt’s manufacturing sector which leans heavily towards capital- and energy-intensive products. This effect is captured in a production function estimated for the twenty industries making up Egypt’s manufacturing sector over the period 2002-2016. With homogeneous parameters, the estimated output elasticity of energy is 0.28. With panel member parameter heterogeneity, the output elasticity of energy is positive and statistically significant in ten manufacturing industries. Negative and statistically significant elasticity is however found in refined petroleum products, fabricated metal products, and electrical machinery and equipment. This indicates suboptimal energy use. Elasticity is also negative, though statistically insignificant, in: textiles, basic metals, and “other manufacturing”. Except for “other manufacturing”, industries of negative elasticity are all energy-intensive. Moreover, refined petroleum, fabricated metals and basic metals are pollution-intensive. A priority policy measure is to remove subsidies from energy inefficient and polluting industries as opposed to mere ‘across-the-board’ removal. Keywords: energy consumption; manufacturing industries; energy- and pollution intensive; Egypt